Cyperus tuckerianus (Cyperaceae), a new species from the Central-West Region of Brazil - Pereira-Silva, Luciana; Hefler, Sonia Marisa; Trevisan, Rafael (Phytotaxa, 2016)
Cyperus tuckerianus is a new species described to the Central-West Region of Brazil. This species is similar to Cyperus unioloides, Cyperus lanceolatus var. compositus and Cyperus lanceolatus var. subunioloides, however the new species is distinguished by its lax anthela, simple or compound with spikelets digitiform or grouped in glomerules, by the size of the spikelets and anthers and narrower rachilla. Morphological description, illustration, identification key, data about the habitat and comparisons with similar species are presented.